Solid Waste Collection and Disposal Practices in Bekwarra Local Government Area: Environmental Impacts and Community Awareness - , Omang, Donald Ikwun, Okon, Aniekanabasi Jonathan, Nji, Elizabeth L-B, Ndulue, Obiageri A. (Archives of Current Research International, 2025)
Background: Waste poses a threat to public health and the environment if it is not stored, collected and disposed of properly. This study investigates the different solid waste collection and disposal practices and its effect on the environment in Bekwarra Local Government of Cross River State. Methods: This study utilized a cross sectional descriptive approach where a self-developed questionnaire and an observation checklist to gather relevant information on solid waste disposal practices were used to collect data. A total of 400 female adults were interviewed in this study. Results: A total of 400 participants completed and returned the questionnaires giving a response rate of 99.2%. Results from the study showed that majority of the respondents produced vegetable waste (15%) while a few of the respondents produced food waste (3%). The study also showed that the use of open containers by the indigenes was the most common method practice with 61.8% while the lest method practice was the use of sack bags (2.5%). It was observed that majority of the respondents 364 (91%) had knowledge of solid waste disposal while 36 (9.6%) had no knowledge of solid waste disposal. Results from the observation checklist showed that only 163 (41%) of respondents had storage containers for waste compared to 235 (59%) without storage containers. Conclusions: It is investigated during the research that due to rapid growth in population, increments in solid waste generation rate, management deficiencies, lack of legislative implementation and funding, the solid waste management systems in Bekwarra are not working effectively. Thus, an inefficient municipal solid waste management system may create serious negative environmental impacts like infectious diseases, land and water pollution, obstruction of drains and loss of biodiversity.